The Educational Impacts of Needs National Economic Empowerment and Development Strategy (Needs) on Poverty Reduction in Sokoto State, Nigeria - Kebbi, Haruna Sani Birnin (2023)
Poverty is a global phenomenon and its consequences are dehumanising and traumatic. Several programmes and policies have been implemented in Nigeria in order to enhance economic progress and lead to a reduction in poverty. One of such programmes is the National Economic Empowerment and Development Strategy (NEEDS). The NEEDS encompassed all sectors of the Nigerian economy so that the impact would be wholesome. Education is certainly one of the sectors that was given much attention by the NEEDS programme. There seems to be no study on the impact of the NEEDS education policy on poverty reduction, especially in Sokoto State. This could perhaps be the reason why Sokoto State is perpetually leading the poverty table amongst the States in Nigeria. The objective of this study is to assess the educational impact of the NEEDS programme on poverty reduction in Sokoto State of the northwestern Nigeria. A total of 826 participants and non-participants were sampled in the study area for this purpose. Applied econometric techniques for development economics like the logit and ordered logit regression models, together with differencein- difference estimation technique were used to analyse the data. The results identified marital status, tribe, educational level, occupation, ICT literacy, and equal opportunity for education as germane to the participation in the NEEDS programme. The findings of this study reveal that access to education, equal opportunity to education, skills acquisition, and ICT literacy all have positive and significant relationship with poverty reduction. On policy implication, this study shows that most poor people will continue to suffer when the quality of education is poor. Education should then be planned in accordance with poverty reduction so that the system should not only target poverty reduction but also poverty elimination. This study benefits policy makers, academic research, and government economic planning department.